Effect of Thoracic Epidural Analgesia in Patients of Traumatic Multiple Rib Fractures withNeurotrauma: A Study Done in a SpecializedNeuro-ICU in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2020)
analgesic administration as well as between early and delayed epidural analgesia. Monitoring was done to identify if any complications occur either due to the procedure or anaesthetic or analgesic drug itself.Results: A total number of 100 patients were recruited for this study. Following thoracic epidural analgesia (TEA), pain rating improved in 76.0% cases; coughing was diminished in 78.0% cases, while suctioning was improved in 68.0% cases. Besides, physiotherapy and positioning improvement were found in 68.0% cases and 72.0% cases respectively, while chest expansion was improved in 88.0% cases. Thoracic epidural analgesia was given soon after injury and had given a significant improvement compared with the patients who got the delayed TEA considering in ventilation (78.0% vs. 22.0%) and in mobilization (72.0% vs. 32.0%)(p